The Music Genre Preferences of Malaysian Teenagers Toward Indonesian Music - Rossa, Crecenda Della; Muhammad Jazuli; Suharto Suharto (Universitas Negeri Semarang, 2025)
This study aims to examine the music genre preferences of Malaysian teenagers toward Indonesian music, specifically the Pop and Dangdut genres. The background of the research is based on the growing influence of Indonesian music culture among Malaysian youth. The method used is a quantitative approach with a survey design. The population consisted of 151 Form IV students at SMK Methodist Tanjong Malim, Malaysia, with a random sample of 106 students selected using the Isaac and Michael table. Data were collected through questionnaires and interviews, then analyzed descriptively and in percentages. The results show that 69.8% of respondents preferred Indonesian Pop music, while 30.2% preferred Indonesian Dangdut. These preferences were influenced by environmental factors and ethnic background; students of Chinese and Indian descent tended to be less interested in Indonesian music. The aspects of enjoyment, attention, and willingness toward Indonesian music were found to be high. Respondents favored melodies that are easy to enjoy and lyrics that are relatable to daily life. Their favorite singer was Keisya Levronka. The study concludes that Indonesian Pop music is more popular among Malaysian teenagers. This research contributes to enriching cross-cultural studies in music and international communication in Southeast Asia.